The migration of Africa's intellectual capital: an explorative research on the career trajectories of academics from other African countries to the University of Cape Town, South Africa - Hulsekopf, K (Department of Sociology, 2014)
The dissertation investigates the development of higher education in Africa and points to the phenomenon of migration of African academics to destinations overseas and more recently to South Africa. The research interest derives from South Africa's unique position on the continent to attract academics from overseas including African academics who left their home country. Therefore South Africa's universities play a significant role in return migration of these academics to the continent. This research follows an explorative approach that aims to capture the trajectories of African academics in present day South Africa. The quantitative research provides a picture of the origin and proportion of African academics at South African universities while the qualitative research explores the trajectories of eleven African academics who were at the time of the study employed at the University of Cape Town in South Africa. The research question focuses on the question 'Why are academics from other African countries than South Africa leaving their country of origin?' and 'What motivates African academics to come to South Africa?' Among other, the research also uncovers whether academics who once immigrated to South Africa have intentions to return to their country of origin. The core part of the dissertation contains the presentation of the findings of in-depth interviews with eleven academics from the University of Cape Town. The research also includes the analysis of all 23 South African universities for the year 2011by accessing information from the database of HEDA (Higher Education Data Analyser) with the assistance of the Institution of Planning Department (IPD) of UCT. Here the proportion of academics coming from other African countries, are presented, for the year 2011. Drawing from the literature on higher education in Africa as well as from the interviews with eleven academics, the dissertation illustrates that in regard to the 'brain drain' of African academics, the overall post 1980s imposed neo-liberal regulations set by the World Bank and IMF which channelled public spending and foreign capital towards primary and secondary education, was an important factor leading to the degradation of African universities and consequently contributed to the migration of African academics. The trajectories of the academics illustrate that the majority of the academics left their country of origin for postgraduate studies overseas or in South Africa. However, after the completion of their studies these academics were eager to build an academic career in Africa, whereby South Africa of them became the preferred destinations. Return migration to the country of origin is in most cases only considered after retirement. Nevertheless, they are all engaged in building relationships to institutions or civic organisations in their home country as well as enabling postgraduate students from their home country to come to South Africa for further studies The dissertation suggest further research to examine to what extent these 'knowledge exchanges' and 'educational transfers' between academic diaspora in South Africa and other African countries are fertile for development in the country of origin and in which ways, universities and academics, in their role as 'ideological leader' can contribute to socio-economic and cultural development by establishing sustainable of relationships which are of mutual benefit.